Architectural and Fundamental Analysis of Blockchain: A Comparative Overview of Working Mechanisms, Tokenization, and Data Decentralization - Dedy Sumarhadi; Sunardi Sunardi; Imam Riadi (JURNAL COMPUTECH & BISNIS, 2026)
Blockchain technology has evolved from a nascent peer-to-peer payment system into a paradigm-shifting digital trust infrastructure, fundamentally challenging conventional centralised models. However, a deep understanding of the fundamental technical aspects behind the popularity of crypto assets remains limited. This study aims to: (1) analyse the fundamental architecture of blockchain; (2) evaluate tokenisation mechanisms; and (3) conduct a comparative analysis of its characteristics against traditional database systems. The research employs a qualitative descriptive method utilising a Systematic Literature Review (SLR) approach to synthesise technical literature published between 2023 and 2025. The analysis focuses on consensus mechanisms, the architectural transition from monolithic to modular systems (Layer-2 scaling), and the measurement of decentralisation using the Nakamoto Coefficient. The results indicate that: (1) blockchain offers distinct advantages in data integrity (immutability) and censorship resistance through a distributed append-only ledger structure, standing in sharp contrast to the CRUD (Create, Read, Update, Delete) model of relational databases; and (2) recent innovations such as Zero-Knowledge Proofs and Optimistic Rollups serve as critical solutions to the "Blockchain Trilemma" (balancing scalability, security, and decentralization). This study concludes that blockchain is not an absolute replacement for conventional databases, but rather a specialised solution for ecosystems that require high transparency and "trustless" interactions without a central authority.